Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging of Phospholipid Changes in a Drosophila Model of Early Amyotrophic Lateral Sclerosis. - Jang, H.J.; Le, M.U.T.; Park, J.H.; Chung, C.G.; Shon, J.G.; Lee, G.S.; Moon, J.H.; Lee, S.B.; Choi, J.S.; Lee, T.G.; Yoon, S. (Journal of the American Society for Mass Spectrometry, 2021)
Amyotrophic lateral sclerosis (ALS) is a degenerative disease caused by motor neuron damage in the central nervous system, and it is difficult to diagnose early. Drosophila melanogaster is widely used to investigate disease mechanisms and discover biomarkers because it is easy to induce disease in Drosophila through genetic engineering. We performed matrix-assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI) to investigate changes in phospholipid distribution in the brain tissue of an ALS-induced Drosophila model. Fly brain tissues of several hundred micrometers or less were sampled using a fly collar to obtain reproducible tissue sections of similar sizes. MSI of brain tissues of Drosophila cultured for 1 or 10 days showed that the distribution of phospholipids, including phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidic acid (PA), phosphatidylserine (PS), and phosphatidylinositol (PI), was significantly different between the control group and the ALS group. In addition, the lipid profile according to phospholipids differed as the culture time increased from 1 to 10 days. These results suggest that disease indicators based on lipid metabolites can be discovered by performing MALDI-MSI on very small brain tissue samples from the Drosophila disease model to ultimately assess the phospholipid changes that occur in early-stage ALS.